A study on the curative effect of nobiletin on paraquat induced toxicity in rat - Muhammad Umar Ijaz (Elsevier, 2022)
This research aimed to evaluate the curative impact of nobiletin (NOB) on paraquat (PQ) induced mitochondrial impairment in rats' hepatic tissues. Twenty-four male rats were divided into control, PQ, PQ + NOB, and NOB treated groups. The alanine aminotransferase levels, aspartate aminotransferase, and alkaline phosphatase were increased in the experimental animals after exposure with PQ. A significant decrease in the level of catalase, glutathione peroxidase, superoxide dismutase, glutathione, thiobarbituric acid reactive substances, and reactive oxygen species were recorded in rats exposed to PQ. The mitochondrial TCA cycle enzyme activities, including isocitrate-dehydrogenase, succinate-dehydrogenase, alpha-ketoglutarate dehydrogenase, and malate-dehydrogenase, were reduced in PQ exposed rats. The activities of mitochondrial enzymes including NADH dehydrogenase, coenzyme Q-cytochrome reductase, succinic-coenzyme Q and cytochrome c-oxidase were significantly decreased after the PQ-exposure. PQ administration also reduced the mitochondrial membrane potential. However, the administration of mitochondria with NOB can decrease the toxic effect of the PQ in isolated mitochondria. NOB treatment potentially reduced the damaging effects of the PQ in the mitochondria isolated from hepatic tissues. Thus, the current study revealed that the NOB could attenuate PQ-induced mitochondrial damage in rats' hepatic tissues.